2021
DOI: 10.1186/s12893-021-01319-8
|View full text |Cite
|
Sign up to set email alerts
|

Mortality following emergency laparotomy: a Swedish cohort study

Abstract: Background Emergency laparotomy (EL) is a central, high-risk procedure in emergency surgery. Patients in need of an EL present an acute pathology in the abdomen that must be operated on in order to save their lives. Usually, the underlying condition produces an affected physiology. The perioperative management of this critically ill patient group in need of high-risk surgery and anaesthesia is challenging and related to high mortality worldwide. However, outcomes in Sweden have yet to be studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
2
8
0
Order By: Relevance
“…Previous studies have shown that emergency laparotomy was associated with high mortality and complication rate compared to those elective surgeries 6 , 7 . The reported global incidence rates of mortality and complication during emergency laparotomy range from 13 to 18% at 30 days, increasing to 25% at 24 months and 50% of complication rates, which is five-fold higher than that of elective surgery 6 , 8 . According to a study conducted in Ethiopia, the mortality rate of the patient is 8.1, and the complication rate is 13.5% after an emergency laparotomy 9 .…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have shown that emergency laparotomy was associated with high mortality and complication rate compared to those elective surgeries 6 , 7 . The reported global incidence rates of mortality and complication during emergency laparotomy range from 13 to 18% at 30 days, increasing to 25% at 24 months and 50% of complication rates, which is five-fold higher than that of elective surgery 6 , 8 . According to a study conducted in Ethiopia, the mortality rate of the patient is 8.1, and the complication rate is 13.5% after an emergency laparotomy 9 .…”
Section: Introductionmentioning
confidence: 97%
“…Despite the ASA score's inter-observer consistency being constantly challenged, [25][26][27] it continues to be widely used, and has been proven to be a reliable predictor for surgical mortality. [28][29][30][31][32][33][34][35][36] ASA physical status is commonly used in Australia as a preoperative assessment of patients by anaesthetists. It is incorporated as part of the WHO safety checklist in most operating theatres, making ASA the only formal risk assessment tool required for a patient to undergo surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Both NELA and ACS‐NSQIP have incorporated the American Society of Anaesthesiologists (ASA) score into their algorithms. Despite the ASA score's inter‐observer consistency being constantly challenged, 25–27 it continues to be widely used, and has been proven to be a reliable predictor for surgical mortality 28–36 . ASA physical status is commonly used in Australia as a preoperative assessment of patients by anaesthetists.…”
Section: Introductionmentioning
confidence: 99%
“…Despite documented advances in the modern era, 1 mortality following EL remains substantial worldwide, affecting up to one of every five patients in the first 30 postoperative days in high-quality health care systems. [2][3][4][5] Efforts to standardize perioperative care of EL patients through implementation of predetermined pathways have led to reduction in postoperative mortality. 6 Standardization in contemporary practice requires calculation and consideration of the risks associated with EL before entering the operating room.…”
mentioning
confidence: 99%
“…Emergency laparotomy (EL) is a common procedure performed worldwide for a wide variety of abdominal pathologies. Despite documented advances in the modern era, 1 mortality following EL remains substantial worldwide, affecting up to one of every five patients in the first 30 postoperative days in high-quality health care systems 2–5 . Efforts to standardize perioperative care of EL patients through implementation of predetermined pathways have led to reduction in postoperative mortality 6 .…”
mentioning
confidence: 99%